(3GdLRA GdChd s - (3OhfGdOS(B, (3hGJSfs; (3eGQiC gheGf(B, s ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2007)
(3ebOeI YGeI Mhd fXQjI GdSYQ (B1) (3fXQjI GdWdH (B: (3GdWdH , GdYQV h SYQ GdShb , eQhfI GdWdH GdSYQjI h eaGgje CNQF ddeQhfI , GdefaYI GdbjGSjI h WdH GdeSJgdc , GdefaYI GdJQJjHjI h efMfjGJ GdShGA h GdefaYI GdcdjI h GdefaYI GdMOjI ddONd GdfbOj , GdefaYI GdJQJjHjI h GdeNGWQI (B2) (3fXQjI GdeDSSI (B: (3GdeDSSI hGJNGP GdbQGQGJ , fXQjI GdGfJGL h GdGNJjGQGJ Hjf GdeONdGJ h GdeNQLGJ , OhGd GdJcdaI h GdHQeLI GdNWjI (B3) (3GdGSYGQ aj Xd GdefGaSI (B: (3GSYGQ GdGeO GdbUjQ h GdGeO GdWhjd aj Xd GdefGaSI GdJGeI , GdJhGRf aj Xd GdefGaSI GdJGeI eY HYV GdJWHjbGJ (B4)(3JMdjd GdSYQ aj Xd GdGMJcGQ (B: (3GdGSYGQ aj Xd GdGMJcGQ , GdJejjR GdGMJcGQj Ch GdJejjR GdSYQj (B5)(3GdSYQ aj Xd GdefGaSI ZjQ GdJGeI (B: (3GdefGaSI GdGMJcGQjI , GMJcGQ GdbdI HYV GdfeGPL GdJj JJVef JMbjb CbUi GdGQHGM hHYV GdfeGPL GdJj dG JJVef JMbjb CbUi GdGQHGM (B6)(3CSYGQ GdYfGUQ (B: (3CSYGQ YfGUQ GdGfJGL , GdGLhQ , (B7) (3GdcaGAI GdGbJUGOjI (B: (3GdJhGRf GdYGe h GdQaGgjI GdGbJUGOjI h GdcaGAI aj GdJhGRf GdYGe ddGSYGQ aj Xd GdefGaSI GdJGeI eY hLhO edGMXGJ QjGVjI aj fgGjI cd aUd(B.s
Keywords: (3GdCSYGQs